Using Drought Stressed Corn for Silage, Hay or Grazing - David L. Wright; Henry E. Jowers (EDIS)
SS-AGR-274, a 4-page fact sheet by D.L. Wright and H.E. Jowers, informs producers of the options for using drought-stricken corn as source of nutrients for livestock, with consideration for avoiding poisoning from the high concentration of nitrates. Information on using nitrate test kits and moisture determination using a microwave oven. Published by the UF Department of Agronomy, July 2007.